Moral Commitment in Intimate Committed Relationships: A Conceptualization From Cohabiting Same-Sex and Opposite-Sex Partners. (January 2013) - Pope, Amber L.; Cashwell, Craig S.
The purpose of this study was to examine how a prominent framework of commitment, Johnson's Tripartite Model, fits within the context of cohabiting same-sex and opposite-sex partnerships to test the applicability of the model to diverse types of relationships. Specifically, this study sought to operationalize the dimension of moral commitment, or the extent to which one feels obligated to stay in a relationship, as this construct has yet to be developed in intimate relationships outside of the marital context. The results provide support for Johnson's Tripartite Model and provide researchers and counselors with a conceptualization of moral commitment from partners in cohabiting same-sex and opposite-sex relationships.